2010
DOI: 10.1002/mana.200910122
|View full text |Cite
|
Sign up to set email alerts
|

Complex valued Ray–Singer torsion II

Abstract: In this paper we extend Witten-Helffer-Sjöstrand theory from selfadjoint Laplacians based on fiber wise Hermitian metrics to nonselfadjoint Laplacians based on fiber wise non-degenerate symmetric bilinear forms. As an application we show that results about the asymptotics of the Ray-Singer torsion of self-adjoint Witten deformation, as well as the strategy proposed by Burghelea-Friedlander-Kappeler to derive the comparison of Ray-Singer and Reidemeister torsion, can be extended to nonself-adjoint Witten deform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…There an alternative definition of refined analytic torsion is considered and a conjecture on its relation to the Turaev torsion is formulated. This conjecture has been proved independently by Burghelea and Haller in [13] and Su and Zhang in [29].…”
Section: Open Problemsmentioning
confidence: 77%
“…There an alternative definition of refined analytic torsion is considered and a conjecture on its relation to the Turaev torsion is formulated. This conjecture has been proved independently by Burghelea and Haller in [13] and Su and Zhang in [29].…”
Section: Open Problemsmentioning
confidence: 77%
“…Then the refined analytic torsion ρ an (∇), cf. [27, (4-6), (4-7), (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)], can be written as…”
Section: Comparison With the Refined Analytic Torsionmentioning
confidence: 99%
“…It was shown that the refined analytic torsion is closely related to the Farber-Turaev torsion [5,2,6,16]. Burghelea and Haller [9,8,10] defined the complex-valued Ray-Singer torsion associated to a non-degenerate symmetric bilinear form on a flat vector bundle over a manifold of arbitrary dimension and made an explicit conjecture concerning the relationship between the Burghelea-Haller analytic torsion and the Farber-Turaev torsion. This conjecture was proved up to sign by BurgheleaHaller [10] and in full generality by Su-Zhang [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [30], Su and Zhang used the approach developed by Bismut-Zhang [4,5], making use of the Witten deformation, proved the conjecture in full generality. In [9], Burghelea and Haller proved their conjecture, up to sign, in the case where X is of odd dimensional. Now consider X with the boundary Y = ∅.…”
Section: Introductionmentioning
confidence: 97%